A fuzzy reasoning approach to assess innovation risk in ecosystems - Abreu, António (2019)
This work was partially supported by the Polytechnic Institute of Lisbon through the Projects for Research, Development, Innovation and Artistic Creation (RDI&AC), within the framework of the project ARPIPME -Evaluation of the risk of innovation processes in small and medium enterprises, IPL/2017/ARPIPME/ISCAL. And, itwas also partially supported by FCT, through IDMEC, under LAETA, project UID/EMS/50022/2013.